Transition to adulthood for young people with intellectual disability: the experiences of their families - Leonard, H.; Foley, K.; Pikora, T.; Bourke, J.; Wong, K.; McPherson, L.; Lennox, N.; Downs, Jennepher (Springer, 2016)
Whilst the transition from school to adult roles can be challenging for any adolescent, for those with an intellectual disability it can present as a particularly difficult time both for the individual and their family. The process may involve coordinated planning, collaboration and decision-making among school staff, families and community agencies. This mixed-methods study utilised information from two cohorts: young people with Down syndrome in Western Australia (n = 190) and young people with intellectual disability (of any cause) in Queensland, Australia (n = 150). The parent-report questionnaires administered in both states comprised two parts: part 1 collected information about the individual with intellectual disability including information on health, functioning and service needs, and about specific transition related issues; and part 2 collected information about the health and well-being of their family. The majority (87 %) of parents said that they were involved in decision-making about transition planning but less than two-thirds (59.5 %) of young people were involved in this process. The three most helpful strategies indicated by parents that assisted with transition planning related to the provision of more information about financial assistance, the school transition program and the building of informal community-based supports. A number of themes emerged from the qualitative data which included parents’ views and concerns about the capacity of their young adult to adapt and change to life in adulthood, their difficulty navigating services and programs, issues and challenges around their young person building connectedness, strain on family wellbeing and finances and worry about the longer term future.